2018
DOI: 10.3390/lubricants6030064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Lubrication by Ionic Liquids: Activated Slip and Flow

Abstract: The present study provides molecular insight into the mechanisms underlying energy dissipation and lubrication of a smooth contact lubricated by an ionic liquid. We have performed normal and lateral force measurements with a surface forces apparatus and by colloidal probe atomic force microscopy on the following model systems: 1-ethyl-3-methyl imidazolium bis-(trifluoro-methylsulfonyl) imide, in dry state and in equilibrium with ambient (humid) air; the surface was either bare mica or functionalized with a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…[ 16 ] In some replica experiments, however, the low‐friction regime was not observed and only a single slope was detected (see empty circles, Figure 3a), which reflects that the composition of the confined IL film remained constant upon an increase in load. Our extensive studies [ 15,17 ] of the influence of traces of water on the interfacial structure and on the friction force at mica‐silica contacts have demonstrated that a higher water content at the interface can reduce the prominence of the low friction regime or even eliminate it, as observed here.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…[ 16 ] In some replica experiments, however, the low‐friction regime was not observed and only a single slope was detected (see empty circles, Figure 3a), which reflects that the composition of the confined IL film remained constant upon an increase in load. Our extensive studies [ 15,17 ] of the influence of traces of water on the interfacial structure and on the friction force at mica‐silica contacts have demonstrated that a higher water content at the interface can reduce the prominence of the low friction regime or even eliminate it, as observed here.…”
Section: Resultssupporting
confidence: 62%
“…The investigation of the dependence of friction on velocity in smooth contacts revealed an intricate lubrication behavior. [ 17 ] Depending on the load, friction can increase, decrease, or remain constant with sliding velocity. This was explained through the strength and the dynamics of the interionic interactions at the slip plane via a stress‐assisted thermally activated slip model.…”
Section: Introductionmentioning
confidence: 99%
“…An et al [86] found that the ionic liquid, glycol ether mixtures, at titanium interfaces had a negative friction load dependence, i.e., the friction force decreased with the increase of normal load. Han et al [87] discussed the activated slip and flow of ionic liquid lubricating molecules.…”
Section: Molecular Lubrication 2311 Ionic Liquid Lubricationmentioning
confidence: 99%
“…[28] Studies at the nanoscale have ascribed the lubrication mechanism of ILs to their adsorption and confinement between smooth surfaces, in absence of any mechano-chemical reactions. [4,29,30] The confined ions resist being "squeezed out" when surfaces are compressed, thus resulting in a film that prevents direct contact between the two surfaces. The properties and dynamic behavior of the adsorbed films are dependent on surface chemistry, charges and applied potentials, molecular structures of the ILs, as well as environmental conditions.…”
Section: Introductionmentioning
confidence: 99%